Overview on manufacturing practices and manufacturing capabilities: A perspective from local manufacturers in northern region of Malaysia - Ibrahim, Amlus; Mohtar, Shahimi (UUM College of Business, 2014)
Generally, manufacturing capability is the important factor in running and developing business.Hence, this research is aimed to identifying the relationships of critical factors and ensure the companies can survive in the northern region of Malaysia.Those identified factors are manufacturing practices and manufacturing capabilities.Through the email survey, a total of 89 companies representing various industries had responded. The hypotheses involved were tested using correlation and regression techniques.The results of the study support all the hypotheses. The multiple regression analysis indicates that there are significant relationships among the factors on each criterion to manufacturing capabilities.While hierarchical multiple regression analysis was carried out to test the role of moderating in the relationship between independent variables with dependent variables.The results of the hierarchical multiple regressions indicate that training moderated the relationship between manufacturing practices, knowledge sharing to manufacturing capabilities.It is believed that results of this study will be beneficial for shareholders and directors of companies to apply these manufacturing capabilities.